Self-healing elastomers using supramoecular approaches - Bras AR; Allgaier J; Antonius W; Hintzen Pyckhout (Kautschuk Gummi Kunststoffe, 2012)
Self-healing polymers are interesting because of increased lifetime or reduced failure probability. Supramolecular materials are ideally suited for such applications. In this concept physical bonds like hydrogen bonds are used to build up high molecular weight polymers on networks of lower molecular weight building blocks. The relatively weak physical bonds are reversible. Upon stress they break first but the reversible nature allows reformation. However, the supramolecular approach contains difficulties like the thermal sensitivity of the materials or the slow healing process. We will review synthesis procedures and summarize relevant physical properties for applications.
Keywords: Damage control; Elastomers; Hydrogen bonding; Self healing; Supramolecular chemistry